The Direct Rebound Effect and Energy Efficiency Policy: An Econometric Estimation in the case of Tunisian Transport Sector - Manel, Daldoul; Ahlem, Dakhlaoui (International Journal of Energy Economics and Policy, 2021)
In this paper, we estimate the sensitivity of the fuel and travel demand with respect to the fuel price and the income variation, in the case of the road transport in Tunisia, during the 1987-2016 period, resorting to two different econometric approaches: the error correction model (ECM) and the dynamic model. The price and income elasticity estimation, in the long term and the short term, allow the assessment of the direct rebound effects. We shall show that (1) the dynamic model is considered to be the most appropriate approach for our database; (2) the fuel price increase, in both the short term and long the long term, has a negative impact on the energy consumption. Hence, we recommend the public decision-maker to review his/her energy subsidies, in order to improve the energy efficiency in the road transport sector and to control the CO2 emissions; (3) an increase of the income entails an increase of the energy consumption and, hence, the travel demand; (4) the rebound effects from the fuel price increase will be compensated in the form of a more significant fuel use indicate that if the energy efficiency increases by 1%, 0.21% and 0.29% of the savings resulting. Keywords: Fuel and travel demand elasticities; the rebound effect; the error correction model; the dynamic model. JEL Classifications: L91, Q43, Q54, R48 DOI: https://doi.org/10.32479/ijeep.11456